2007
DOI: 10.1097/mpg.0b013e31812e5710
|View full text |Cite
|
Sign up to set email alerts
|

Ninety Percent of Celiac Disease Is Being Missed

Abstract: Serological screening of 5470 children age 7.5 years from a cohort of 13,971 children in the Avon Longitudinal Study of Parents and Children (ALSPAC) suggested the prevalence of celiac disease (CD) to be at least 1%. ALSPAC is an anonymous study, and hence seropositive children could not be individually identified or undergo biopsy. Inasmuch as all children within ALSPAC suspected of having CD are referred to just 1 center, we aimed to identify children with biopsy-confirmed CD who were likely to be in this co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 19 publications
(23 reference statements)
0
53
0
Order By: Relevance
“…If this is confirmed in other studies, individuals with untreated silent CD may be exposed to the same risk for long-term complications as celiacs with symptomatic disease (1,17,18). This is an argument in favour of a mass-screening for CD in children (19)(20)(21), although many aspects of widespread screening must be considered (15,22). There were 15 children with untreated, screening-detected CD, 36 children with untreated, symptomatic CD and 42 healthy control children.…”
Section: Discussionmentioning
confidence: 77%
“…If this is confirmed in other studies, individuals with untreated silent CD may be exposed to the same risk for long-term complications as celiacs with symptomatic disease (1,17,18). This is an argument in favour of a mass-screening for CD in children (19)(20)(21), although many aspects of widespread screening must be considered (15,22). There were 15 children with untreated, screening-detected CD, 36 children with untreated, symptomatic CD and 42 healthy control children.…”
Section: Discussionmentioning
confidence: 77%
“…Several of the clinical indications listed were more noticeable in the biopsy-negative group, namely, failure to thrive and other high-risk characteristics that might imply CD, such as diabetes mellitus type 1, hypertransaminasemia, and IgA deficiency. All these clinical symptoms may indeed suggest CD (12), but their higher occurrence within the biopsy-negative group intensifies the concept that CD is mainly asymptomatic and the majority of cases remain undiagnosed (7,9,10,16,30). Lurz et al (23) similarly presented failure to thrive as a more pronounced characteristic in the disease control group of highrisk children.…”
Section: Discussionmentioning
confidence: 99%
“…In Sweden, United Kingdom, and Germany the prevalence exceeded in some studies even 1.5% , Mustalahti 2010). However, many children, especially the asymptomatic ones, may remain undiagnosed (Ravikumara 2007). A Swedish screening study revealed that only 1/3 of children with CD had been clinically detected and diagnosed before serological testing (Myléus 2009).…”
Section: Epidemiology Prevalence Of CDmentioning
confidence: 99%